A quality improvement study to improve the utilization of occupational therapy and physiotherapy services in a level 4 neonatal intensive care unit and neurodevelopmental follow-up clinics - Pranay Jindal; Irfana Ajab Shah; Jisha Elizabeth Mathew; Shihab Kannappillil; Ma Lorena Igna Sibayan; Parvathy Ragesh; Sashtha Girish; Irian Jade Cabanillas; Ana Princess Villa; Matheus Franciscus Petrus Van Rens; Mohamed Rami Alturk; Mohamad Adnan Mahmah; et al. (CHRISMED Journal of Health and Research, 2023)
Background: Neonates admitted to the neonatal intensive care unit (NICU) are at risk of neuromotor and behavioral impairments, and therapy services can optimize their neurodevelopment. Physiotherapy (PT) and Occupational therapy (OT) services are available in the NICU of Women's Wellness and Research Center, and as per the guidelines, physicians should refer the neonates for appropriate services. Baseline analysis of 1-month data revealed that 25%, 36%, 62%, and 10% of eligible neonates were not referred to (1) inpatient OT, (2) inpatient PT, (3) baby therapy, and (4) neonatal neurodevelopmental clinic, respectively. The study's objective is to increase the number of babies being referred, by reducing the number of eligible neonates not being referred to 4 available therapy services to 50% of the baseline data after 1 month of implementation. Methods: A Plan-Do-Study-Act cycle guided the interventions. The 1st phase identified stakeholders' challenges for not referring the babies to appropriate services. Based on their feedback, the referral criteria were revised. The 2nd phase involved implementing the revised criteria. Steps included (a) stakeholders' education on the revised criteria and making it available all the time, (b) daily triage and huddle to inform stakeholders of the needed referrals, and (c) establishing communication pathways. Results: Exceeding the targets, all eligible and 75% of the eligible neonates for neonatal neurodevelopmental and baby therapy clinics, respectively, were referred. For inpatient OT and PT services, 22% (targeted 12.5%) and 20% (targeted 18%) of the eligible neonates were missed. Conclusion: Within 1 month, we decreased the number of nonreferrals to all 4 therapy services. Inpatient PT and OT referrals need more focus.